2018
DOI: 10.21660/2018.47.47589
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Analysis of Land Use in Bumiaji Subdistrict, Batu City, East Java, Indonesia

Abstract: ABSTRACT:The Bumiaji area is an upstream river basin that has undergone land changes from an undeveloped to a developed area, which may cause a disturbance in the river basin. This research investigates the river basin using secondary data covering land use, land slope, rainfall, and soil types. The quality indicator of a river basin is measured from the quantity of surface runoff. The bigger the scale of the surface runoff is, the lower the quality of the river basin. This research aims to examine the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Over 2003-2007, the settlement area increased by 9%, plantation and farms increased by 7%, and the forest area decreased by 6%. The watershed response can be observed through the increasing of run-off coefficient from 0.59 to 0.67 [143] and an increase in peak discharge (at the outflow of the sub-watershed) from 96.8 m 3 s −1 in 2003 to 189.2 m 3 s −1 in 2007 [144]. Meanwhile the springs were affected (data to be further collected) and groundwater recharge was probably reduced.…”
Section: Appendix A5 Tropical Peatland Restoration In Indonesiamentioning
confidence: 99%
“…Over 2003-2007, the settlement area increased by 9%, plantation and farms increased by 7%, and the forest area decreased by 6%. The watershed response can be observed through the increasing of run-off coefficient from 0.59 to 0.67 [143] and an increase in peak discharge (at the outflow of the sub-watershed) from 96.8 m 3 s −1 in 2003 to 189.2 m 3 s −1 in 2007 [144]. Meanwhile the springs were affected (data to be further collected) and groundwater recharge was probably reduced.…”
Section: Appendix A5 Tropical Peatland Restoration In Indonesiamentioning
confidence: 99%
“…the level of slope and slope position) have an effect on the level of surface runoff and soil erosion. In addition, the previous research that was conducted in the upstream Brantas watershed showed the increases of runoff coefficient in the steep of topography with disturbed area by agricultural and human activities (Witjaksono et al, 2018). The runoff and soil erosion will carry water from the highest point to the lowest point along with different amounts of nutrients and parts of the topsoil.…”
Section: Introductionmentioning
confidence: 95%
“…Bumiaji Sub-District is located in the mountainous area with a high-risk level of landslides caused by high hazards and vulnerability [5]. The land-use conversion from protected forest to agriculture in Sub-Brantas Upstream affected the high frequency of landslide events [6]. Throughout 2017-2022, 45 landslide events affect physical, social, and economic losses.…”
Section: Introductionmentioning
confidence: 99%